2019
DOI: 10.1029/2019jc015109
|View full text |Cite
|
Sign up to set email alerts
|

Inorganic Carbon and pCO2 Variability During Ice Formation in the Beaufort Gyre of the Canada Basin

Abstract: Solute exclusion during sea ice formation is a potentially important contributor to the Arctic Ocean inorganic carbon cycle that could increase as ice cover diminishes. When ice forms, solutes are excluded from the ice matrix, creating a brine that includes dissolved inorganic carbon (DIC) and total alkalinity (AT). The brine sinks, potentially exporting DIC and AT to deeper water. This phenomenon has rarely been observed, however. In this manuscript, we examine a ~1 year pCO2 mooring time series where a ~35‐μ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 60 publications
2
19
0
Order By: Relevance
“…Ecosystem and biogeochemical analyses targeting estimation of biological production rates in both water and sea ice, and characteristics of dissolved organic and inorganic matter, are another focus, with papers employing syntheses of multimodel experiments in combination with collective data analysis (e.g. Dainard et al, 2019;DeGrandpre et al, 2019;Ji et al, 2019;Watanabe et al, 2019).…”
Section: Beaufort Gyre Phenomenon: Multicomponent System Mechanisms and Changesmentioning
confidence: 99%
See 1 more Smart Citation
“…Ecosystem and biogeochemical analyses targeting estimation of biological production rates in both water and sea ice, and characteristics of dissolved organic and inorganic matter, are another focus, with papers employing syntheses of multimodel experiments in combination with collective data analysis (e.g. Dainard et al, 2019;DeGrandpre et al, 2019;Ji et al, 2019;Watanabe et al, 2019).…”
Section: Beaufort Gyre Phenomenon: Multicomponent System Mechanisms and Changesmentioning
confidence: 99%
“…The data set analyzed in the paper serves as a valuable baseline for future estimates of biological production rates. Journal of Geophysical Research: Oceans DeGrandpre et al (2019) show how inorganic carbon export from the surface layers is related to sea ice formation. Modeling of the ecosystem is performed by Watanabe et al (2019), who conducted an intercomparison of ice algal productivity in the Chukchi and Barents seas and in the Eurasian and Canada basins at seasonal to decadal scales employing five different models.…”
Section: Ecosystem and Biogeochemistry Dynamicsmentioning
confidence: 99%
“…Steele and Dickinson (2016) also found that SST is typically <0°C at DOR. Ice melt and formation could change pCO 2 by diluting and concentrating DIC, respectively, and by altering the ratio of DIC and A T in the ice or brine (Cai et al, 2010;DeGrandpre et al, 2019;Rysgaard et al, 2007Rysgaard et al, , 2009. Ice melt occurs before DOR and could decrease pCO 2 levels (Cai et al, 2010).…”
Section: 1029/2020gl088051mentioning
confidence: 99%
“…The pCO 2 was then recalculated using the new DIC, SST, and salinity and a constant total alkalinity (A T ) in the CO 2 equilibrium program CO2sys (Pierrot et al, 2006). The A T was estimated using an A T -salinity relationship derived from bottle samples during the BGOS cruises (DeGrandpre et al, 2019;Yamamoto-Kawai et al, 2005). A T is a conservative property of seawater that does not change with temperature or air-sea CO 2 exchange (Millero, 2007).…”
Section: 1029/2020gl088051mentioning
confidence: 99%